ANALYSIS OF EMPLOYEE SAFETY, HEALTH AND WORK DISCIPLINE PROGRAMS ON WORK PRODUCTIVITY CASE STUDY AT PT. WISMA KARYA ANDALAS - Arnida, Arnida; Thata, Salmiyah; Meda, Tamrin (Jurnal Edueco, 2024)
This research aims to analyze the extent of the influence of the implementation of the Occupational Safety and Health (K3) program and the implementation of the work discipline program on employee work productivity. This research uses a survey method, sampling using a purposive sampling technique, which is determining a sample from the entire population with certain criteria so that the results of the analysis produce a conclusion that the employee empowerment variable (X1) has a very significant influence on performance, the t-count value is obtained 3.508 with a significance value or probability value of 0.018, which is much smaller than 0.05. Then the work discipline variable (X2) on work productivity is obtained with a t-count value of 3.036 with a significance value or probability value of 0.025 < 0.05. Thus, the influence of the Occupational Safety and Health Program (X1) and Work Discipline (X2) on employee Work Productivity, the results of data analysis using SPSS obtained an F count value of 22.096 with a significance level of 0.000 or smaller than the significance level used, which is 0.05 (0.000 < 0.05). This provides an overview that the variables of occupational safety and health and work discipline together have a significant influence on the work productivity of employees at PT. Wisma Karya Andalas.Abstract has no more than 200 words written in a paragraph. If the article is in Bahasa Indonesia then the abstract is written in Bahasa Indonesia and English. The abstract section contains the problems and objectives of research, research procedures, and summary of research results. (TNR, 11 italic, single spaced).